A Comparative Analysis of Operational Efficiency between Chinese and Indian Commercial Banks - Nan Zhu; Huajie Zhang (The Central European Review of Economics and Management (CEREM), 2018)
Aim: The objective of this paper is to make comparative analysis on operational efficiency between Chinese and Indian commercial banks (CBs).~Design / Research methods: Following the previous scholars' study, two models with different sets of input and output variables have been used to show how efficiency scores vary with change in inputs and outputs. The efficiency scores are measured by using data envelopment analysis (DEA) approach.~Conclusions / findings: The mean technical efficiency score of Chinese CBs is always relatively higher than the corresponding score of Indian CBs in 2012-2013, respectively. In terms of technical efficiency and pure technical efficiency, the performance of foreign banks in China is always relatively lower than that of foreign banks in India.~Originality / value of the article: While many similar studies have evaluated the performance of banking industries in different countries, very few studies have evaluated the performance of banking sectors between Chinese and Indian economies. The paper would be of interest for OR scholars and practitioners in financial industry.~Implications of the research (if applicable): The next step of this study could collect more samples and use Malmquist index method to conduct further study on efficiency, efficiency changing and productivity, in order to conduct further competitive power analysis on both of banking industries of China and India.
Keywords: 330; Data envelopment analysis; Commercial banks; China; India